2012
DOI: 10.4103/0019-5413.104186
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical evaluation of proximal femoral nail antirotation with respect to helical blade position in femoral head: A cadaveric study

Abstract: Objective:Despite new developments in the management of osteoporotic fractures, complications like screw cutout are still found in the fixation of proximal femur fractures even with biomechanically proven better implants like proximal femoral nail antirotation (PFNA). The purpose of this cadaveric study was to investigate the biomechanical stability of this device in relation to two common positions (center-center and inferior-center) of the helical blade in the femoral head in unstable trochanteric fractures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Biomechanical studies have shown that the blade has a higher resistance to head collapse than commonly used screw design [ 11 , 14 ]. The first biomechanical study of the PFNA device suggests that the inferior position of the helical blade in the frontal plane and center position in the sagittal plane is superior to the center-center position in both planes and provides better biomechanical stability [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have shown that the blade has a higher resistance to head collapse than commonly used screw design [ 11 , 14 ]. The first biomechanical study of the PFNA device suggests that the inferior position of the helical blade in the frontal plane and center position in the sagittal plane is superior to the center-center position in both planes and provides better biomechanical stability [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Center-center placement is recommended. All blades to migrate an acceptable distance but do so statistically less in center-center followed by center-inferior placement compared to others [16,17] . Reduction with slight valgus is greatly described in both sliding hip screw and intramedullary devices.…”
Section: Discussionmentioning
confidence: 99%
“…Three black markers 1 mm in diameter, which were not located collinearly, were placed at the front of the femoral head. Each specimen was positioned so that it could move within the 3D space defined by the calibration frame [22]. Two cameras were placed at 30° to the center of the specimen to measure the migration of the proximal fragment according to each axis (x-, y-, and z-axes) (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…This test was carried out by applying a load of 1400 N [25]. However, the final load value was set to 750 N because of the occurrence of femoral shaft fracture at 1100 to 1200 N [22]. The loading protocols were as follows.…”
Section: Methodsmentioning
confidence: 99%